Inside Back Cover: Catalytic Reaction Rates Controlled by Metal Oxidation State: C−H Bond Cleavage in Methane over Nickel‐Based Catalysts (Angew. Chem. Int. Ed. 13/2017). Issue 13 (20th February 2017) - Che, Fanglin; Ha, Su; McEwen, Jean‐Sabin
Abstract : Riding high on a wave of positivity :Methane C−H activation over nickel clusters is promoted by low concentrations of surface carbon, interfacial carbide species, or an increase in the local oxidation state of nickel in response to a positive electric field. In their Communication on page 3557 ff., J.‐S. McEwen, S. Ha, and F. Che deliver fundamental insights into the role of surface carbon and electric field within an electrochemical device for hydrocarbon conversion.